Robust resource allocation algorithm for heterogeneous wireless networkwith SWIPT - Yongjun XU; Yuan HU; Guoquan LI; Jinzhao LIN; Qianbin CHEN (Tongxin xuebao)
To improve energy efficiency and robustness of heterogeneous wireless networks with wireless information and power transfer,the robust joint transmit power and power splitting resource allocation problem was studied.Based on mini-max probability machine and Dinkelbach method,the original NP-hard problem was transformed into a solvable convex optimization form,meanwhile a distributed dual resource allocation algorithm was proposed.Additionally,both computational complexity and robust sensitivity were analyzed.Simulation results show that the proposed algorithm can guarantee the quality of service requirements of macro cellular users and femtocell users under channel uncertainties.